The modeling of the yielding capacity of winter cereals due to satellite monitoring data of agricultural lands in Ukraine - Stupen, Roman; Ryzhok, Zoriana; Stupen, Nazar; Stupen, Oksana (Geodesy and Cartography, 2021)
The paper reveals the method of work in the geoinformation system Crop Monitoring on the basis of satellite monitoring data on the example of comparison of two neighboring land uses outside Bortkiv village council of Zolochiv district of Lviv region. One has determined the size of the areas of crops of winter cereals and deduced the dependence between the index of the vegetative index NDVI and their yield capacity on the basis of the estimation of the state of land use by the processing of space information. One has suggested to take into account the value of NDVI when calculating the yield of winter cereals using mathematical modeling. The results obtained from the satellite monitoring data are proposed to be used for the planning of winter cerels yields, determining the area of their sowing and optimizing the harvesting time.